2016
DOI: 10.2215/cjn.07900715
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TWEAK and Major Adverse Cardiovascular Events in Patients with CKD

Abstract: Background and objectives Soluble TNF-like weak inducer of apoptosis (sTWEAK) is a proinflammatory cytokine belonging to the TNF superfamily. sTWEAK concentrations have been associated with the presence of CKD and cardiovascular disease (CVD). We hypothesized that sTWEAK levels may relate to a higher prevalence of atherosclerotic plaques, vascular calcification, and cardiovascular outcomes observed in patients with CKD.Design, setting, participants, & measurements A 4-year prospective, multicenter, longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
2
8
1
Order By: Relevance
“…independent since it has been demonstrated that TWEAK induces macrophage differentiation into osteoclasts in the presence of OPG, indicating a different mechanism of action (29). Confirming data of previous works (19)(20), we observed that sTWEAK levels are independently associated with CV events in CKD patients.…”
Section: However Effects Of Tweak and Opg In Vascular Calcification supporting
confidence: 89%
See 1 more Smart Citation
“…independent since it has been demonstrated that TWEAK induces macrophage differentiation into osteoclasts in the presence of OPG, indicating a different mechanism of action (29). Confirming data of previous works (19)(20), we observed that sTWEAK levels are independently associated with CV events in CKD patients.…”
Section: However Effects Of Tweak and Opg In Vascular Calcification supporting
confidence: 89%
“…In addition, loss-of function experiments have shown that TWEAK increases atherosclerotic plaque calcification (15). Finally, circulating soluble TWEAK (sTWEAK) levels have been associated with cardiovascular outcomes in CKD patients (19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…However, neither traditional risk factors, risk score charts for general population nor emerging risk biomarkers appear to significantly increase the prediction power in this population. [ 2 4 ] Thus, classical risk prediction equations underestimate cardiovascular disease risk in adults with CKD [ 5 , 6 ] and new tools for risk prediction in renal patients are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, TWEAK has been indicated as predictor of mortality in dialysis and non-dialysis CKD patients, as well as a biomarker of CVD outcomes [215]. Moreover, it has been observed that atherosclerotic burden and atheromatosis progression in CKD patients free of CVD are accompanied by low TWEAK, suggesting that TWEAK could serve as biomarker to predict CVD risk even before clinical manifestations [216,217].…”
Section: Role Of Trail Opg and Tweak In Cardiovascular Disease Of Cmentioning
confidence: 99%